Îlot textuel et d’autres formes de la représentation du discours autre dans un corpus de textes de presse - Chovancová, Katarína (Verbum – Analecta Neolatina, 2008)
The paper focuses on the presence of reported speech in journalistic texts. It concentrates on the role of quotation marks as introducers of reported speech elements, marking not only voices different from the author’s one, but also pieces of reference sets that are not his own. Words and segments introduced by quotation marks thus show fragments of foreign discourses and foreign individual and social identities. The distance taken by the journalist from the other people’s words will be examined on a corpus of French journalistic texts.